Penerapan Model Difusi Inovasi Dalam Adopsi Teknologi Hidroponik Indoor Di Kawasan Agroeduwisata Cikundul Sukabumi: Sebuah Pendekatan Strategis Dalam Transformasi Agrikultur Edukatif Dan Berkelanjutan: The Application of the Diffusion of Innovation Model in the Adoption of Indoor Hydroponic Technology in the Cikundul Agro-edu-tourism Area, Sukabumi: A Strategic Approach to Transforming Educational and Sustainable Agriculture - Lutfi Hilmi Rafael; Amanda Aulia Zahirah; Fahri Ramadhan Nugrayasa; Karina Supriatna; Naula Usamah; Nazwa Alya Izabella (Jurnal Agritechno, 2026)
This study explores the integration of social innovation and technological advancement in the development of indoor hydroponic farming at the Agroeduwisata Cikundul Area (KAC), under the Department of Food Security. KAC aims to empower local communities through sustainable agriculture education, production, and conservation. This paper identifies the early-stage implementations as a testing ground for indoor hydroponic systems utilizing LED lighting to address spatial and climate limitations. Drawing from interviews and observational data, the study examines how community participation, collaboration with educational institutions, and limited resources influence the process. The results highlight the importance of social cohesion, adaptive infrastructure, and inclusive planning in the success of community-based agro-innovation. These findings contribute to broader discussions on rural technology adoption and agroecological sustainability.